Mexican university students’ perceptions about gender roles - Hernández Herrera, Claudia Alejandra (Acta Universitaria, 2019)
The aim of this research was to study Mexican university students’ perceptions on gender roles at home and at the job market. This was carried out through a survey using a Likert type scale questionnaire. It is a transversal study with a sample of 1408 students, where the factor analysis and generalized linear models were conducted. Four factors were found: 1) women and housework, 2) men and family, 3) job market, and 4) offspring care and education. It is concluded that education institutions should commit to implement awareness programs oriented towards education on gender equality and to strengthen their strategies on vulnerable youth groups coming from disadvantaged socio-economic groups.